Social Learning Analytics in Higher Education. An experience at the Primary Education stage - Jose Javier Díaz-Lázaro; Isabel M. Solano Fernández; María del Mar Sánchez-Vera (Springer, 2017)
The concept of Learning Analytics, as we understand it today, is relatively new but the practice of evaluating user behavior is not innovative. For years, technological development, along with other educational aspects, have encouraged, developed and facilitated this practice as a way of providing a personalized quality experience to students. The main goal of this study, carried out in the Primary Education Degree of the University of Murcia, was to research, from the perspective of Social Learning Analytics, how students learn and collaborate in online environments, specifically through their use of social media. With the idea of improving and optimizing future teaching experiences, a pilot study was conducted using weblog, Twitter and Facebook to work with different topics on the subject. The method used in this research was a participant observation and the analysis performed was both quantitative, based mainly on the data gathered from the learning analytics, and qualitative (analyzing students' content from comments). Results show that there was greater interaction on Facebook than weblogs, where students interacted to deal with aspects related to the learning process and the topic of the subject. This exchange of information grew during the development of the experience. In addition, learning analytics shows that there is a relationship between group members and their interaction and behavior in networks.